Prevalence of impaired renal function in virologically suppressed people living with HIV compared with controls: the Copenhagen Comorbidity in HIV Infection (COCOMO) study*. Issue 10 (29th July 2019) - Petersen, N; Knudsen, AD; Mocroft, A; Kirkegaard‐Klitbo, D; Arici, E; Lundgren, J; Benfield, T; Oturai, P; Nordestgaard, BG; Feldt‐Rasmussen, B; Nielsen, SD; Ryom, L
Abstract : Objectives: While renal impairment is reported more frequently in people living with HIV (PLWH) than in the general population, the PLWH samples in previous studies have generally been dominated by those at high renal risk. Methods: Caucasian PLWH who were virologically suppressed on antiretroviral treatment and did not have injecting drug use or hepatitis C were recruited from the Copenhagen Comorbidity in HIV Infection (COCOMO) study. Sex‐ and age‐matched controls were recruited 1:4 from the Copenhagen General Population Study up to November 2016. We defined renal impairment as one measurement of estimated glomerular filtration rate ≤ 60 mL/min/1.73 m 2, and assessed associated factors using adjusted logistic regression models. The impact of HIV‐related factors was explored in a subanalysis. Results: Among 598 PLWH and 2598 controls, the prevalence of renal impairment was 3.7% [95% confidence interval (CI) 2.3–5.5%] and 1.7% (95% CI 1.2–2.2%; P = 0.0014), respectively. After adjustment, HIV status was independently associated with renal impairment [odds ratio (OR) 3.4; 95% CI 1.8–6.3]. In addition, older age [OR 5.4 (95% CI 3.9–7.5) per 10 years], female sex [OR 5.0 (95% CI 2.6–9.8)] and diabetes [OR 2.9 (95% CI 1.3–6.7)] were strongly associated with renal impairment. The association between HIV status and renal impairment became stronger with older age ( P = 0.02 for interaction). Current and nadir CD4 counts, duration of HIV infection and previous AIDS‐defining diagnosis were not associated with renal impairment among virologically suppressed PLWH. Conclusions: The prevalence of renal impairment is low among low‐risk virologically suppressed Caucasian PLWH, but remains significantly higher than in controls. Renal impairment therefore remains a concern in all PLWH and requires ongoing attention.